C-terminal telopeptide procollagen type I change in patients with atrial fibrillation - A. V. Goryachiy; A. I. Gozhenko; E. M. Levchenko; V. V. Goriachyi; M. A. Kuznetsova; M. I. Arapu (Journal of Education, Health and Sport, 2017)
Method: C-terminal telopeptide procollagen type –I (CTTP-I) was used as a marker for collagen synthesis. The study group comprised 69 people and the control group 23. Results: Patients with persistent and chronic AF had an elevated level of CTTP-I in comparison with patients with paroxysmal AF (0.40+0.19 ng/ml, 0.44+0.21 ng/ml vs 0.36+0.17 ng/ml, p=0.016). The level of CTTP-I was significantly lower in the control group compared to patients with paroxysmal, persistent and chronic AF forms (0.36+0.17 ng/ml, 0.40+0.19 ng/ml, 0.44+0.21 ng/ml and 0.27+0.11ng/ml , p=0.016). Conclusions: The level of CTTP-I is significantly different between healthy people and patients with AF. Moreover, these markers also differ depending on the AF form. It can be assumed that the intensity of extracellular synthesis and degradation of type I collagen can be related to the severity and type of AF.